The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1017/s0047279400017426
|View full text |Cite
|
Sign up to set email alerts
|

Dependency and Ageing in Britain: A Re-Examination of the Evidence

Abstract: There has been growing concern over the consequences for public expenditure of an increasing number of elderly people dependent on a relatively diminishing working population. This concern stems largely from demographically determined dependency ratios and it is not necessarily the case that a change in the age profile of the population will lead to a greater burden of dependency. The 'engine of dependency' is shown to have at least two other cylinders-patterns of labour-force participation across age and gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…It has been suggested that dependency levels projected to the end of the century have been overestimated and that 'current and short-future problems regarding dependency levels are likely to relate to the state of the economy rather than to age pyramids'. 68 Other writers have indicated that assumptions about costs have been based on stable levels of disability-dependency in the elderly population while the indications are that the improved health of younger cohorts as they age will reduce costs. 69 The claim that growing cohorts of elderly people with money will extend the consumer market 70 -71 appears not to stand up under close scrutiny, since this category represent a small proportion of the elderly population.…”
Section: The Costs Of Dependency and Disabilitymentioning
confidence: 99%
“…It has been suggested that dependency levels projected to the end of the century have been overestimated and that 'current and short-future problems regarding dependency levels are likely to relate to the state of the economy rather than to age pyramids'. 68 Other writers have indicated that assumptions about costs have been based on stable levels of disability-dependency in the elderly population while the indications are that the improved health of younger cohorts as they age will reduce costs. 69 The claim that growing cohorts of elderly people with money will extend the consumer market 70 -71 appears not to stand up under close scrutiny, since this category represent a small proportion of the elderly population.…”
Section: The Costs Of Dependency and Disabilitymentioning
confidence: 99%
“…As a result of the significant increase in life expectancy during this century, the number of people reaching this age in Britain has grown from 2.2 million in 1901 to 9.7 million in 1981 (Falkingham, 1989). In 1980, 88 per cent of men in this age group were actually retired from work (Turner, 1984).…”
Section: Social Death and The Elderlymentioning
confidence: 99%
“…In the section which follows, we will try to clarify the meaning of 'social death' by examining two influential American studies in which this concept was first employed for purposes of sociological interpretation. More recent work has shown that the conclusions of these studies have considerable relevance for present day Britain (Field 1989).…”
Section: T H E C H a N G I N G P R O F I L E O F S O C I A L D E A T Hmentioning
confidence: 99%
“…As a result of the significant increase in life expectancy during this century, the number of people reaching this age in Britain has grown from 2.2 million in 1901 to 9.7 million in 1981 (Falkingham 1989). In 1980, 88 % of men in this age group were actually retired from work (Turner 1984).…”
Section: Social Death and The Elderlymentioning
confidence: 99%